Enteropathogen Identification by Multiplex PCR in Guatemalan Children with Acute, Non-bloody Diarrhea. (4th October 2017) - Melgar, Mario; Lamb, Molly; Calvimontes, Diva M; Asturias, Edwin J; Contreras-Roldan, Ingrid; Dominguez, Samuel; Robinson, Christine C; Berman, Stephen; Gaensbauer, James
Abstract: Background: Diarrhea is a leading cause of morbidity and mortality in children in low and middle income countries (LMICs). Assessing diarrhea etiology in LMICs is of great importance in order to better develop both therapeutic and public health strategies, but is hampered by the complexity of potential diarrheal pathogens, and diverse methodology needed for pathogen identification Methods: Subjects 6 to 35 months old with acute, moderate severity, non-bloody diarrhea were enrolled in a diarrheal treatment trial, conducted at one rural ( N = 172) and two urban sites ( N = 144) in Guatemala. Diarrheal pathogens were determined in stool by multiplex PCR (FilmArray GI® Biofire) which allows simultaneous identification of 23 bacterial, viral, parasitic pathogens. Descriptive statistics on demographics, pathogen load, and differences in pathogen occurrence by site were performed; differences were assessed with t-test and chi 2 test Results: Nearly all (96.8%) subjects had pathogens identified, and most had multiple potential pathogens identified (mean pathogen count: 2.7 urban and 4.8 rural; P < 0.001 (Figure 1). Notable pathogen differences were observed between rural and urban populations. Bacteria (particularly E.coli pathotypes and Campylobacter) and protozoa (particularly giardia) were more common in the rural population (Figure2). Viral pathogens were either similar or more common (norovirus; P = 0.04) in the urban population; rotavirus was uncommon in both sites (10 rural and 12 urban cases). A similar pattern of pathogen evolution with patient age was noted in both settings, with a decrease in the relative number of viral and increase in parasitic pathogens (Figure 3). Important demographic and socioeconomic differences between rural and urban were noted: rural subjects had poorer nutritional status, underdeveloped water and sanitation facilities and more domestic animal exposure Conclusion: Acute diarrheal episodes in Guatemalan children were associated with a complex spectrum of pathogens when determined by multiplex PCR, with distinct patterns in rural and urban populations. Future studies to precisely determine diarrheal etiologies in LMICs will need to incorporate controls to sort causative organisms from those colonizing the intestine. Disclosures: All authors: No reported disclosures.